Why there are and will be less deaths in India due to COVID-19: an insight - Vasantrao, Chincholikar Sanjeev (International Journal Of Community Medicine And Public Health, 2020)
Coronavirus disease (COVID-19) is an infectious disease caused by a newly discovered coronavirus. Most people infected with the COVID-19 virus will experience mild to moderate respiratory illness and recover without requiring special treatment. It has been declared a pandemic by the World Health Organization which exhibited human-to-human transmissibility and spread rapidly across countries. Older people, and those with underlying medical problems like cardiovascular disease, diabetes, chronic respiratory disease, and cancer are more likely to develop serious illness. Climate, with temperature, humidity, Bacillus Calmette–Guérin (BCG) vaccination, immune status of persons, elderly people, uncontrolled co morbid conditions like heart diseases, diabetes mellitus, hypertension, kidney diseases seems to play an important role in spread and severity of corona virus infection. As reported from MOHFW website, the COVID-19 deaths are more in above 60 years of age with comorbidities cardiovascular disease, diabetes, chronic respiratory disease, and cancer.